Dynamics of Feeding for Infants, Young Children, and Families. Issue 4 (July 2016) - N/A,
Abstract : Feeding problems in infants and children have a major impact on families. Nurses are committed to providing family-centered care and are uniquely positioned to help improve family-focused feeding care. This special issue on feeding problems in infants and children covers a wide range of issues and offers evidence that nurses have the opportunity to influence positive outcomes when feeding problems are encountered. Each of the articles provides important information for neonatal and pediatric nurses.